Airborne measurements of BrO and the sum of HOBr and Br2 over the Tropical West Pacific from 1 to 15 km during the CONvective TRansport of Active Species in the Tropics (CONTRAST) experiment. Issue 20 (31st October 2016) - Chen, Dexian; Huey, L. Gregory; Tanner, David J.; Salawitch, Ross J.; Anderson, Daniel C.; Wales, Pamela A.; Pan, Laura L.; Atlas, Elliot L.; Hornbrook, Rebecca S.; Apel, Eric C.; Blake, Nicola J.; Campos, Teresa L.; et al.
Abstract: A chemical ionization mass spectrometer was used to measure BrO and HOBr + Br2 over the Tropical West Pacific Ocean within the altitude range of 1 to 15 km, during the CONvective TRansport of Active Species in the Tropics (CONTRAST) campaign in 2014. Isolated episodes of elevated BrO (up to 6.6 pptv) and/or HOBr + Br2 (up to 7.3 pptv) were observed in the tropical free troposphere (TFT) and were associated with biomass burning. However, most of the time we did not observe significant BrO or HOBr + Br2 in the TFT and the tropical tropopause layer (TTL) above our limits of detection (LOD). The 1 min average LOD for BrO ranged from 0.6 to 1.6 pptv and for HOBr + Br2 ranged from 1.3 to 3.5 pptv. During one flight, BrO observations from the TTL to the extratropical lowermost stratosphere were used to infer a profile of inorganic bromine (Br y ). Based on this profile, we estimated the product gas injection of bromine species into the stratosphere to be 2 pptv. Analysis of Br y partitioning further indicates that BrO levels are likely very low in the TFT environment and that future studies should target the measurement of HBr or atomic Br. Key Points: BrO observations throughout the tropics from 1 to 15 km were typically below a limit of detection of 1 pptv and were compatible with zero BrO and HOBr were observed at significant levels in biomass burning plumes in the tropical free troposphere Model calculations indicate that BrO is a minor constituent of Bry in the tropics and highlight the importance of measuring HBr in the future